The Influence of Green Marketing and Green Knowledge on Purchase Intention: The Moderating Role of Gender - Sahrizal Putra (Lensa Ilmiah: Jurnal Manajemen dan Sumberdaya, 2026)
Growing environmental concerns have encouraged businesses to adopt green marketing strategies and promote sustainable consumption practices. However, the effectiveness of different green marketing dimensions and environmental knowledge in shaping consumers’ purchase intention remains inconclusive, particularly within experience-based coffee businesses. This study aims to examine the effects of green product, green place, green price, green promotion, and green knowledge on consumers’ purchase intention at Kopi Klotok Yogyakarta, as well as to investigate the moderating role of gender in the relationship between green knowledge and purchase intention. A quantitative explanatory survey design was employed using data collected from 178 consumers through an online questionnaire. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that green product, green price, green promotion, and green knowledge have significant positive effects on purchase intention, whereas green place does not significantly influence purchase intention. Among all predictors, green knowledge emerged as the strongest determinant, highlighting the importance of environmental awareness in shaping sustainable consumption behavior. Furthermore, gender was found not to moderate the relationship between green knowledge and purchase intention, suggesting that environmental knowledge affects purchasing intentions similarly among male and female consumers. The model explains 62.1% of the variance in purchase intention (R² = 0.621), indicating substantial explanatory power. These findings contribute to the green marketing literature by emphasizing the dominant role of environmental knowledge and demonstrating that the effectiveness of green marketing dimensions is context-dependent within experience-based coffee businesses. Practically, the results suggest that businesses should prioritize environmental education, environmentally friendly products, fair pricing strategies, and credible sustainability communication to strengthen consumers’ purchase intention.